Efficacy and safety of adjunctive topiramate for schizophrenia: a meta‐analysis of randomized controlled trials. (1st September 2016) - Zheng, W.; Xiang, Y.‐T.; Xiang, Y.‐Q.; Li, X.‐B.; Ungvari, G. S.; Chiu, H. F. K.; Correll, C. U.
Abstract : Objective: To systematically examine the randomized controlled trial (RCT) evidence regarding efficacy and tolerability of topiramate cotreatment with antipsychotics in schizophrenia‐spectrum disorders. Methods: Random‐effects meta‐analysis of RCTs of topiramate cotreatment with antipsychotics vs. placebo/ongoing antipsychotic treatment in schizophrenia‐spectrum disorders. Standardized or weighted mean difference (SMD/WMD), risk ratio (RR) ±95% confidence intervals (CIs), and number needed to harm (NNH) were calculated. Results: Across 16 RCTs ( n = 934, duration = 11.8 ± 5.6 weeks), topiramate outperformed the comparator regarding change/endpoint of total (SMD: −0.58, 95% CI: −0.82, −0.35, P < 0.00001), positive (SMD: −0.37, 95% CI: −0.61, −0.14, P = 0.002), negative (SMD: −0.58, 95% CI: −0.87, −0.29, P < 0.0001), and general symptoms (SMD: −0.68, 95% CI: −0.95, −0.40, P < 0.00001). Furthermore, topiramate was superior regarding body weight (WMD: –2.75 kg, 95% CI: −4.03, −1.47, P < 0.0001), body mass index (BMI) (WMD: –1.77, 95% CI: −2.38, −1.15, P < 0.00001), triglycerides ( P = 0.006), and insulin levels ( P < 0.00001). Superiority regarding psychopathology and body weight/BMI was consistent across Chinese/Asian and Western RCTs, double‐blind and open designs, clozapine and non‐clozapine cotreatment, augmentation and co‐initiation RCTs, and higher and lower quality RCTs. In meta‐regression analyses, topiramate's efficacy for total symptoms was moderated by shorter illness duration ( P = 0.047), while weight loss was greater in prevention/co‐initiation vs. intervention/augmentation RCTs (−4.11 kg, 95% CI: −6.70, −1.52 vs. −1.41 kg, 95% CI: −2.23, −0.59, P < 0.001). All‐cause discontinuation was similar between topiramate and comparators (RR: 1.28, 95% CI: 0.91, 1.81, P = 0.16). While topiramate led to more concentration/attention difficulties ( P = 0.03, NNH = 8, 95% CI=4–25), psychomotor slowing ( P = 0.02, NNH = 7, 95% CI = 4–25), and paresthesia ( P = 0.05, NNH = 2, 95% CI = 4–33), it led to less ≥7% weight gain ( P = 0.0001, NNH = 2, 95% CI = 2–3) and constipation ( P = 0.04, NNH = 9, 95% CI = 5–100) than the comparator. Conclusions: These results indicate that adjunctive topiramate to antipsychotics is an effective and safe treatment choice for symptomatic improvement and weight reduction in patients with schizophrenia‐spectrum disorders.